Istri-istri Sukarno - Nuryanti, Reni, 1983- (Yogyakarta : Ombak, 2007)
Brief biographies of Soekarno's wives
Daftar bacaan : p. [265]-268
Keywords: Soekarno, -- 1901-1970; Presidents' spouses -- Indonesia -- Biography